A Portrait of Self-Branding on Social Media: Understanding Islamic Values and Trends in The Digital Native Generation - Maya Sabrina; Dhiajeng Putri N (Journal of Religion, Local Politics, and Law, 2026)
The growth of social media has transformed how digital-native generations construct and present identity. Islamic college students face a unique challenge in balancing digital trends with Islamic values. This study examines self-branding patterns and strategies among students at Sunan Ampel State Islamic University, Surabaya, focusing on Instagram and TikTok and the integration of Islamic values. Using a qualitative case study approach, data were collected through in-depth interviews, social media observation, and documentation of six selected students, and analyzed using Miles and Huberman’s model and Goffman’s dramaturgical framework. The findings show that students consciously curate content as digital self- presentation (front stage), while the selection process and consideration of Islamic values occur in the back stage. Self-branding combines modern visual aesthetics, personal narratives, and religious symbols presented in popular, contextual forms. Students experience dual pressures from religious expectations and social media algorithms, yet gain opportunities for networking, reputation building, and digital da’wah. The study concludes that student self-branding at UIN Sunan Ampel Surabaya represents a hybrid identity adapting Islamic values to contemporary digital culture.